The Combined Measurement of Pelvic Organ Mobility and Hiatus Area Improves the Sensitivity of Transperineal Ultrasound When Detecting Pelvic Organ Prolapse - Xiaoduo Wen; Haiyan Tian; Xiaojing Yan; Quiqing Sun; Yuanyuan Du; Denggui Wen; Yi Yang (Frontiers in Medicine, 2021)
Objective: To evaluate whether the combined measurement of pelvic organ mobility and levator hiatus area improves the sensitivity of transperineal ultrasound (the index test) for diagnosing pelvic organ prolapse (POP).Methods: We retrospectively recruited women who had been examined in a tertiary gynecological center for symptoms of lower urinary tract incontinence and/or POP between January 2017 and June 2018. We excluded patients who had undergone hysterectomy previously or those who had received corrective surgery. All subjects underwent a standardized interview, POP quantification (POP-Q) examination (a reference standard for patients and controls), and ultrasound measurements of the levator hiatus area at rest (rHA), on contraction (cHA), and on Valsalva (vHA). We also determined the mobility of the bladder neck (BNM), cervix (CM), and rectum ampulla (RAM). Receiver operating characteristic (ROC) curve analyses were performed to determine cut-off values for diagnosis. Diagnostic performance was assessed by sensitivity, specificity, and area under curve (AUC).Results: A total of 343 women were eligible for analysis, including 247 POP patients (stage 2–3 by POP-Q) and 96 controls. Compared with controls, POP cases had significantly higher values for rHA, vHA, cHA, BNM, CM, and RAM. Each parameter was identified as a significant discriminator for POP and controls, as determined by ROC curve analysis, although the cut-off value varied slightly between different parameters. The combination of rHA, vHA, and cHA (with any HA that was ≥ the cut-off) improved the sensitivity from 64–89 to 89–93%. The combination of pelvic organ mobility with rHA, vHA, and cHA, further increased the sensitivity from 89–93 to 95–97%.Conclusion: The combination of levator hiatus area and pelvic organ mobility improved the sensitivity of transperineal ultrasound in the diagnosis of POP, whether used as a frontline test to assist POP-Q grading or to monitor the effect of pelvic floor exercise programs.